Immune-related adverse events with immune checkpoint inhibitors affecting the skeleton: a seminal case series. Issue 1 (11th October 2018) - Moseley, Kendall F.; Naidoo, Jarushka; Bingham, Clifton O.; Carducci, Michael A.; Forde, Patrick M.; Gibney, Geoffrey T.; Lipson, Evan J.; Shah, Ami A.; Sharfman, William H.; Cappelli, Laura C.
Abstract : Background: The use of immune checkpoint inhibitors is increasing in cancer therapy today. It is critical that treatment teams become familiar with the organ systems potentially impacted by immune-related adverse events associated with these drugs. Here, we report adverse skeletal effects of immunotherapy, a phenomenon not previously described. Case presentations: In this retrospective case series, clinical, laboratory and imaging data were obtained in patients referred to endocrinology or rheumatology with new fractures ( n = 3) or resorptive bone lesions ( n = 3) that developed while on agents targeting PD-1, CTLA-4 or both. The average age of patients was 59.3 (SD 8.6), and five were male. Cancer types included melanoma, renal cell carcinoma and non-small cell lung cancer. All fracture patients had vertebral compression, and two of the three had multiple fracture sites involved. Sites of resorptive lesions included the shoulder, hand and clavicle. Biochemically, elevated or high-normal markers of bone resorption were seen in five of the six patients. Erythrocyte sedimentation rate was elevated in three of the four patients where checked. Conclusions: This case series represents the first description of potential skeletal adverse effects related to immune checkpoint inhibitors. These findings are important for providers caring for patients who experience musculoskeletal symptoms and may merit additional evaluation.